POTENSI FRAKSI DAUN SIRIH MERAH (Piper crocatum) MENGHAMBAT JAMUR PENYEBAB KEPUTIHAN - Puspitasari, Dewi Fitriani; Kresnawati, Yani; Sebtiana K, Rika (Jurnal Buana Farma, 2025)
Vaginal discharge is a condition suffered by many women, both adolescents and menopausal women. This is due to hormonal changes and imbalances in normal flora, as well as fungal infections such as Candida albicans. Several studies have tested the activity of red betel leaf fractions against Candida albicans using 70% and 80% ethanol solvents in the extraction process. This study aims to test the activity of n-hexane and ethyl acetate fractions of red betel leaf against Candida albicans extracted using 96% ethanol solvent. The study began with extraction using 96% ethanol solvent, followed by phytochemical screening of the extract. Fractionation was carried out with n-hexane, ethyl acetate, and water solvents. The n-hexane and ethyl acetate fractions were then tested for their activity against Candida albicans. The results showed that the n-hexane fraction exhibited greater inhibitory activity against Candida albicans than the ethyl acetate fraction (p<0.05), indicating that the n-hexane fraction is more potent in inhibiting Candida albicans.